Writing and Publishing : the Librarian's Handbook. - Smallwood, Carol (ALA Editions, 2009)
"Writing and Publishing" will serve as a great resource, whether in taking the anxiety out of writing or refining your style, you'll use this book as much as your pen or keyboard!